Examining the design, manufacturing and analytics of smart wearables. Issue 3 (4th June 2020) - Lopez, Ximena; Afrin, Kahkashan; Nepal, Bimal
Abstract: Recent advancements in sensors, device manufacturing and big data technologies have enabled the design and manufacturing of smart wearables for a wide array of applications in health care. These devices can be used to remotely monitor and diagnose various diseases and aid in the rehabilitation of patients. Smart wearables are an unobtrusive and affordable alternative to costly and time‐consuming healthcare efforts such as hospitalization and late diagnosis. Developments in micro‐ and nanotechnologies have led to the miniaturization of sensors, hybrid 3D printing of flexible plastics, embedded electronics and intelligent fabrics, as well as wireless communication mediums that permit the processing, storage and communication of data between patients and healthcare facilities. Due to these complex component architectures that comprise smart wearables, manufacturers have faced a number of problems, including minimum sensor configuration, data security, battery life, appropriate user interfaces, user acceptance, proper diagnosis and many more. There has been a significant increase in interest from both the academic and industrial communities in research and innovation related to smart wearables. However, as smart wearables integrate several different aspects such as design, manufacturing and analytics, the existing literature is quite widespread, making it less accessible for researchers and practitioners. The purpose of this study was to narrow this gap by providing a state‐of‐the‐art review of the extant design, manufacturing and analytics literature on smart wearables—all in one place—thereby facilitating future work in this rapidly growing field of research and application. Lastly, it also provides an in‐depth discussion on two very important challenges facing the smart wearable devices, which include barriers to user adoption and the manufacturing technologies of the wearable devices.